2021
DOI: 10.1002/term.3228
|View full text |Cite
|
Sign up to set email alerts
|

In vitro maturation using an agarose matrix with incorporated extracellular matrix proteins improves porcine oocyte developmental competence by enhancing cytoplasmic maturation

Abstract: Here, we present a novel in vitro maturation (IVM) system comprising an agarose matrix supplemented with extracellular matrix (ECM) proteins for enhanced maturation of immature oocytes within cumulus–oocyte complexes (COCs) derived from porcine medium antral follicles (MAFs). Immunocytochemical analyses of integrin subunit α2, α5, α6, β1, and β4 expression suggested that integrin α2β1, α5β1, α6β1, and α6β4 play pivotal roles in IVM of porcine immature oocytes. Combinatorial supplementation of fibronectin inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…In recent years, studies on three-dimensional (3D) cell cultures have seen a wave of interest that led to the creation of accurate physiological and pathological models [ 10 ]. Specific 3D systems were also developed to support oocyte IVM in different species: alginate microbeads [ 11 ], agarose matrix [ 12 ] or glass scaffolds [ 13 ]. In 2016, we developed a microbioreactor using liquid marbles (LM) consisting of a polytetrafluoroethylene (PTFE) particle bed, as a novel system to support ovine oocyte IVM in small volumes [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, studies on three-dimensional (3D) cell cultures have seen a wave of interest that led to the creation of accurate physiological and pathological models [ 10 ]. Specific 3D systems were also developed to support oocyte IVM in different species: alginate microbeads [ 11 ], agarose matrix [ 12 ] or glass scaffolds [ 13 ]. In 2016, we developed a microbioreactor using liquid marbles (LM) consisting of a polytetrafluoroethylene (PTFE) particle bed, as a novel system to support ovine oocyte IVM in small volumes [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Type I collagen encoded by the COL1A1 and COL1A2 genes as well as Type VI collagen encoded by COL6A1 and COL6A2 are prominent components of the ECM and are found throughout the ovary (Iwahashi et al, 2000;Berkholtz et al, 2006). The positive effect of collagen on the porcine oocyte IVM maturation has also been observed by using an agarose matrix with ECM proteins, including collagen (Park et al, 2021). Another report has indicated that embedding COCs in collagen gel enhances the meiotic competence of canine oocytes (Otoi et al, 2006).…”
Section: Discussionmentioning
confidence: 97%
“…Intracellular signals can be rapidly and reversibly altered through changes in the conformation of integrins without altering their expression levels (Monniaux et al, 2006). In the ovary, the ECM influences the function of granulosa cells (Huet et al, 2001) and promotes cytoplasmic maturation of oocytes (Park et al, 2021). Integrins have been shown in sheep (Fujiwara et al, 1997), mice (Kitasaka et al, 2018) and cattle (Ohira et al, 2013) to be an essential mediator in follicle organization.…”
Section: Ovarymentioning
confidence: 99%